2022
DOI: 10.7554/elife.66005
|View full text |Cite
|
Sign up to set email alerts
|

Species-specific sensitivity to TGFβ signaling and changes to the Mmp13 promoter underlie avian jaw development and evolution

Abstract: Precise developmental control of jaw length is critical for survival, but underlying molecular mechanisms remain poorly understood. The jaw skeleton arises from neural crest mesenchyme (NCM), and we previously demonstrated that these progenitor cells express more bone-resorbing enzymes including Matrix metalloproteinase 13 (Mmp13) when they generate shorter jaws in quail embryos versus longer jaws in duck. Moreover, if we inhibit bone resorption or Mmp13, we can increase jaw length. In the current study, we un… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 228 publications
(320 reference statements)
0
4
0
Order By: Relevance
“…Such alterations may encompass changes in bone matrix hardness and the cytokine profile, such as interleukin (IL) and tumor necrosis factor (TNF)-α. During the inflamed state, the dysregulated activity of TGF-β signaling may reverse the inhibition of cell proliferation ( 26 , 27 ). This reversal in turn can lift the inhibitory restrictions tumor cells, contributing to their aberrant growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such alterations may encompass changes in bone matrix hardness and the cytokine profile, such as interleukin (IL) and tumor necrosis factor (TNF)-α. During the inflamed state, the dysregulated activity of TGF-β signaling may reverse the inhibition of cell proliferation ( 26 , 27 ). This reversal in turn can lift the inhibitory restrictions tumor cells, contributing to their aberrant growth.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, TGF-β may enhance the migratory and invasive capabilities of tumor cells ( 28 , 29 ), enabling them to infiltrate neighboring tissues, blood vessels or lymphatic vessels. Simultaneously, TGF-β may also dampen the immune system's ability to identify and eliminate tumors ( 27 , 29 ). It was also noteworthy that chronic stress and the sympathetic nervous system may have involvements in the tumor in the present cases, where the persistent inflammation may have activated the sympathetic nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that there are marked species differences in TGF-β signaling pathway ( Kruithof et al, 2012 ). For example, chickens had significantly higher TGF-β signaling activity in lower jaw skeleton than ducks ( Smith et al, 2022 ). Chickens and mice exhibited distinct TGF-β ligand expression patterns during the epithelial to mesenchymal cell transformation ( Azhar et al, 2003 ; Molin et al, 2003 ) and had contradictory requirements for the TGF-β ligands and receptors during the endocardial-to-mesenchymal cell transformation ( Jiao et al, 2006 ; Yamagishi et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…understanding the early evolution and evolvability of neural crest derived structures, including teeth and jaws [41,42]. Past research on jaw length regulation suggests that the anatomy of Alienacanthus most likely resulted from derived modifications in one or multiple pathways involving the transforming growth factor-beta, the bone morphogenetic proteins, the sonic hedgehog pathway members or the fibroblast growth factor [43][44][45]. In halfbeak fishes specifically, the calmodulin molecule paralogue calm1, known to play a generic role in bone cell proliferation, was identified as a potential regulator of jaw length, with its differential expression in upper and lower jaws [46].…”
Section: Extreme Jaw Elongation and Modularity Through Timementioning
confidence: 99%